2006
DOI: 10.1007/s00248-006-9071-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acetate- or Methanol-Assimilating Bacteria under Nitrate-Reducing Conditions by Stable-Isotope Probing

Abstract: Stable-isotope probing (SIP) was used to identify acetate- or methanol-assimilating bacteria under nitrate-reducing conditions in activated sludge. A sludge sample obtained from wastewater treatment systems was incubated in a denitrifying batch reactor fed with synthetic wastewater containing [(13)C]acetate or [(13)C]methanol as the main carbon source and nitrate as the electron acceptor. We analyzed how growth of bacterial populations was stimulated by acetate or methanol as the external carbon source in nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 45 publications
5
108
1
Order By: Relevance
“…Recently, Arcobacter strains were isolated from the graphite electrode of a microbial fuel cell inoculated with marine sediment and fed with acetate (Fedorovich et al, 2009) (Figure 5), indicating that Arcobacter species are able to use acetate and transfer electrons onto solid-phase electron acceptors. In a recent cultivation-independent SIP study with estuarine sediment, Arcobacter-related bacteria incorporated 13 C into their DNA from acetate and glucose under various terminal electron acceptor conditions (aerobic, nitrate-, sulfate-reducing, methanogenic) (Osaka et al, 2006;Webster et al, 2010). Under sulfatereducing conditions with 13 C-labeled acetate, Arcobacter became enriched fast and although the authors suggested that Arcobacter was involved in sulfur cycling, iron and manganese reduction during the sediment incubations were indicated by increasing concentrations of dissolved manganese and iron (Webster et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Arcobacter strains were isolated from the graphite electrode of a microbial fuel cell inoculated with marine sediment and fed with acetate (Fedorovich et al, 2009) (Figure 5), indicating that Arcobacter species are able to use acetate and transfer electrons onto solid-phase electron acceptors. In a recent cultivation-independent SIP study with estuarine sediment, Arcobacter-related bacteria incorporated 13 C into their DNA from acetate and glucose under various terminal electron acceptor conditions (aerobic, nitrate-, sulfate-reducing, methanogenic) (Osaka et al, 2006;Webster et al, 2010). Under sulfatereducing conditions with 13 C-labeled acetate, Arcobacter became enriched fast and although the authors suggested that Arcobacter was involved in sulfur cycling, iron and manganese reduction during the sediment incubations were indicated by increasing concentrations of dissolved manganese and iron (Webster et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…M. parvicella was believed not to reduce nitrite to nitrogen gas [22]. However, many other bacteria could reduce nitrite, such as the members of Rhodobacteraceae (accounting for 8.1 and 5.2% respectively for the ASB and ISB libraries) and Hyphomicrobium (accounting for 2.0 and 2.1% respectively for the ASB and ISB libraries) [32]. Thus the denitrification performance was not adversely affected, either, as indicated by the equivalent TN removals (68.5-83.6% during sludge bulking period vs. 66.5-75.5% during non-bulking period).…”
Section: Bulking Impact On Bacterial Populations Related To Nutrient mentioning
confidence: 99%
“…Previous research isolated TB127-79 from activated sludge in a circulation flush toilet (Hoshino et al 2006), while BXHB27 has been found in activated sludge from a wastewater treatment plant. The 12C-M17 and PHOS-HE19 have been identified from microbial communities in nitratereducing (Osaka et al 2006) and phosphorus-removal ecosystems (Dabert et al 2001), respectively. These four bacteria are frequently found in aerobic activated sludge or domestic wastewater treatment equipment.…”
Section: Dominant Groups and Their Distribution Characteristicsmentioning
confidence: 99%